Identifikasi Kecenderungan Persepsi Investasi sebagai Respon Isu Investasi Bodong Pada Mahasiswa di Universitas Islam Majapahit - Fitri Isnaini, Nurdiana; Verlandes, Yuliasnita; Hadi Purnomo, Agoes (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Issues are the basis for forming perceptions because often the issues that develop influence a person's perception. The negative issue of fraud under the guise of investment will of course have a big influence on the formation of investment perceptions. Students are a group that easily accepts issues through intensive interaction with communication media so that students are a group that is quite dynamic in forming investment perceptions. This research aims to analyze students' gender tendencies in forming investment perceptions and to analyze the influence of negative issues about fraud under the guise of investment on the formation of investment perceptions. The research method used in this research was a survey method on 381 students in Malang City. The research was conducted when there were many negative issues surrounding fraud under the guise of investment in 2017. The results of the research showed that investment perception was still quite low, namely the average score was 5.58 or 55.8% of the maximum score. The average investment perception for women is higher than men, namely 5.7. Men's investment perception score is lower, namely 5.36, this shows that women are more interested in investing than men.